Alokasi Belanja Rutin dan Belanja Modal pada Indeks Pembangunan Manusia Tahun Anggaran 2015-2017 - Kakadir, Petrus; Suaryana, I Gusti Ngurah Agung; Putri, I Gusti Ayu Made Asri Dwija; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p04, 2021)
This study aims to determine the effect of routine and capital expenditure allocations on the human development index in the regency/municipality of Papua province. This study covers 29 districts/cities in the province of Papua using an associative quantitative approach. The analysis technique used is multiple linear regression analysis technique. The results of the analysis show that routine expenditures have a positive and significant effect on the human development index, while capital expenditures have a negative and non-significant effect on the human development index. The failure of capital expenditures to affect the human development index occurred, in addition to the low amount of capital expenditure allocated in an effort to improve people's welfare, also due to the allocation of capital expenditures that had not been carried out on target. Keywords: Routine Shopping; Capital Expenditures; Human Development Index.